2016
DOI: 10.7196/sarj.2016.v22i1.60
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile and clinical correlates in HIV-exposed infants with severe (hypoxic) pneumonia

Abstract: <p><strong>Introduction. </strong>Severe pneumonia in infants who are HIV-infected is a common problem in many parts of the developing world, especially sub-Saharan Africa. What has been missing from previous studies of severe pneumonia in HIV-infected infants, however, is a description of the host inflammatory response and cytokine/chemokine profile that accompanies this disease.</p><p><strong>Objective.</strong> To describe the cytokine profiles associated with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Furthermore, previous reports have indicated that severe pneumonia is associated with methicillin-resistant S. aureus carrying the staphylococcal cassette chromosome mec type IV and Panton-Valentine leukocidin genes ( 12 , 13 ). Furthermore, a recent study reported that high expression of interleukin-10 ( IL-10 ) and interferon-induced protein ( IP-10 ) in human immunodeficiency virus-infected infants were associated with more severe hypoxic pneumonia ( 14 ). The IL-6–174 GG genotype is correlated with lower severity and mortality in patients with pneumococcal CAP ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous reports have indicated that severe pneumonia is associated with methicillin-resistant S. aureus carrying the staphylococcal cassette chromosome mec type IV and Panton-Valentine leukocidin genes ( 12 , 13 ). Furthermore, a recent study reported that high expression of interleukin-10 ( IL-10 ) and interferon-induced protein ( IP-10 ) in human immunodeficiency virus-infected infants were associated with more severe hypoxic pneumonia ( 14 ). The IL-6–174 GG genotype is correlated with lower severity and mortality in patients with pneumococcal CAP ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of metalloproteinase-9 (MMP-9) in peripheral blood circulation in patients with CAP caused by Mycoplasma pneumoniae is increased in the acute phase of illness compared to the control group [ 11 ]. Furthermore, a recent study has reported that high expression of IL-10 and interferon-induced protein (IP)-10 in human immunodeficiency virus (HIV)-infected infants is associated with more severe hypoxic pneumonia [ 12 ]. However, currently, no study has reported the association of long non-coding RNAs (lncRNAs) with pneumonia.…”
Section: Introductionmentioning
confidence: 99%